IEEE VSSS Dynamic Model Identification Using Standard Maneuvers - Ribeiro, Daniele de Souza Sales; Coelho, Mariana de Moura Cunha; Souza, Elianfrancis Silveira de; Santiago, Mariane Sabino; Santos Neto, Accacio Ferreira dos (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
Identifying dynamic models of mobile robots, par-ticularly in the IEEE Very Small Size Soccer (VSSS) category, poses significant challenges due to the nonlinear nature and parametric complexity of their dynamics. This work proposes an approach to identify the dynamic model of a VSSS robot based on standard operational maneuvers, employing the interior-point method for parameter estimation. For validation purposes, five models were developed based on different scenarios constructed from these maneuvers. The results demonstrate that the proposed methodology is capable of producing models that satisfactorily represent the robot's dynamic behavior. In particular, models based on forward and coupled movements exhibited superior performance and more consistent generalization capability, pro-viding a solid foundation for future advances in control strategies and autonomy of mobile robotic systems.